PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP MOTIVASI BELAJAR PAI PESERTA DIDIK SMPN 1 WATULIMO - Dilla Yulia Safitri; Ramadina , Evy (STAI Pelabuhan Ratu, 2026)
This research is driven by the dominance of the lecture-based learning model, which triggers boredom and decreasesstudents' learning motivation in Islamic Education (PAI). The purpose of this study is to empirically examine the influence of the Student Teams Achievement Division (STAD) type of cooperative learning model on the learning motivation of seventhgrade students at SMPN 1 Watulimo. The research method employed is a quantitative approach with a quasi-experimental design. The research sample was selected using a purposive sampling technique, divided into experimental and control classes. The primary data collection instrument was a validated learning motivation questionnaire, with data analysis techniques performed using SPSS 25. Statistical analysis resultsindicate that the STAD cooperative model has a significant influence on students' learning motivation. This is supported by the homogeneity of variance test(Levene’s Test) results, showing a significance value of 0.464 (> 0.05), indicating homogeneous data variance. Furthermore, there is a difference in the average motivation questionnaire scores, where the experimental class scored 6.38 points higher than the control class. In conclusion, the STAD model is effective in increasing psychological drive and student enthusiasm in Islamic Education learning. The implications of this research suggest the use of the STAD model as a strategy to create a more dynamic and participatory learning ecosystem.